Phenolic compounds from Callistemon citrinus leaves and stems - Khanh, Pham Ngoc; Đuc, Ho Viet; Huong, Tran Thu; Ha, Vu Thi; Van, Doan Thi; Son, Ninh The; Kim, Young Ho; Viet, Do Quoc; Cuong, Nguyen Manh (Vietnam Journal of Science and Technology, 2016)
In the search for bioactive constituents from Vietnamese plants,  the leaves and stems of Callistemon citrinus (Curtis) Skeels were selected for chemical investigation. Phytochemical analysis of plant led to the isolation of eight phenolic compounds including two flavonoids (eucalyptine (1) and 8-demethyleucalyptine (2)), two alcohols (blumenol A (3), n-tetratriacontanol (4)), three benzoic acid derivatives (acid gallic (5), methyl gallate (6) protocatechuic acid (7)), one sterol (b-sitosterol (8)), and along with one sesquiterpene (2,6,10-bisabolatriene (9)). The structures of the natural compounds were determined by spectroscopic evidences including 1D- and 2D-NMR and ESI-MS.